FIRST RECORD OF THE INCIDENCE OF THE COCONUT MITE, ACERIA (ERIOPHYES) GUERRERONIS KEIFER IN NIGERIA - C.I. Aisagbonhi; R.V. Nair; K.O. Kolade (International Coconut Community Journal, 2004)
In continuation of the search for the causes of premature nutfall of coconut palms in Nigeria, samples of fresh fallen nuts were examined under the microscope. Coconut palms (Chowghot Dwarf green (Indian), Malayian Dwarf yellow and Malayian Dwarf orange were surveyed between May to August 2003. The button stage nuts and premature nuts that recently fell on the ground were picked and conveyed back to the laboratory. The perianth (calyx ends) of each nut were split opened and examined under the microscope for presence of mites. Aceria(Eriophyes)guerreronis population were assessed per nut. All three ecotypes examined were infested. Preliminary observations indicated a mean mite population of 187.94 + 17.92 per nut sampled.Mealybugs (Pseudococcus sp) and some unidentified mites were also observed. The role of these mites in the incidence of premature nutfall of coconut palms is discussed in this paper.